2018
DOI: 10.1007/s00040-018-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

Colony size and brood investment of Myrmica rubra ant colonies in habitats invaded by goldenrods

Abstract: Ant richness and abundance are negatively affected by the invasion of alien goldenrods (Solidago sp.). However, little is known about the mechanisms standing behind the impact of the invaders on ant life history, such as colony investments in growth and reproduction. We examined this problem of the investments of Myrmica rubra ant colonies living in different grasslands invaded and non-invaded by goldenrods. Altogether, 47 colonies were analysed; and for each colony, we calculated the number of queens, workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Invasive plants can induce negative changes in ground-dwelling arthropod assemblages ( Schirmel et al 2011 ; Gallé et al 2015 ), usually by altering habitat structure ( Hejda et al 2009 ), but also by changing the nesting site ( Somogyi et al 2017 ) or food availability ( Lenda et al 2013 ; Trigos-Peral et al 2018 ). The results of our previous studies performed on M. rubra ants living in meadows invaded by Solidago plants ( Lenda et al 2013 ; Grześ et al 2018 ; Trigos-Peral et al 2018 ) suggest that there can be different selective pressures on ant colonies living in these two habitat types thus we expected to find the differences in individual and/or colony personalities. Our results did not demonstrate such differences but found that the behavior of Myrmica workers and colonies can differ at three levels of variation (among- and intraindividual variation, and also in residual variation).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Invasive plants can induce negative changes in ground-dwelling arthropod assemblages ( Schirmel et al 2011 ; Gallé et al 2015 ), usually by altering habitat structure ( Hejda et al 2009 ), but also by changing the nesting site ( Somogyi et al 2017 ) or food availability ( Lenda et al 2013 ; Trigos-Peral et al 2018 ). The results of our previous studies performed on M. rubra ants living in meadows invaded by Solidago plants ( Lenda et al 2013 ; Grześ et al 2018 ; Trigos-Peral et al 2018 ) suggest that there can be different selective pressures on ant colonies living in these two habitat types thus we expected to find the differences in individual and/or colony personalities. Our results did not demonstrate such differences but found that the behavior of Myrmica workers and colonies can differ at three levels of variation (among- and intraindividual variation, and also in residual variation).…”
Section: Discussionmentioning
confidence: 93%
“…Higher Myrmica nest density results in lower predictability of individual activity but allospecific nest density had an opposite effect (foragers had higher predictability in their activity). This can highlight the importance of competition for food and nesting sites which has an enhanced effect on seminatural meadows (see also Lenda et al 2013 ; Grześ et al 2018 ). Competition is usually considered to have a significant effect in shaping ant communities ( Savolainen and Vepsäläinen 1988 ; Braschler and Baur 2003 ; Trigos-Peral et al 2016 ), and unavoidably occurs when the ecological requirements of species overlap ( Pianka 1974 ; Glen and Dickman 2008 ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations